Akselerasi Pemberdayaan Masyarakat Desa Gondang Melalui Optimalisasi Pemanfaatan Potensi Lokal - Maryono Maryono (LPPM Press, 2015)
The main target of the obligatory rural social internships for university students’program (KKN-PPM) is to increase the gross enrollment rate (APK) of secondaryand higher education in Gondang village society, which can directly improve theHuman Development Index (HDI). In addition, KKN-PPM is projected to createsociety self-reliance, by optimizing the local potency of the village. KKN program forsociety empowerment is an option to raise the potency and overcome all the existingproblems in the Gondang village as well as strengthen the global commitment of theyear 2000, on the establishment of aims and targets of the Millennium DevelopmentAges or Millenneum Development Goals (MDGs). This community empowerment isestablished, guided and developed as a social institution in the form of friendship forums,advocacy, communication, education and, activity medium to strengthen integratedfamily functions that is established and carried out from, by and for their families andcommunities. Thus, the principle of transfering science and technology can be fulfilled.Because there is a flow of solution from the campus intellectuals, and as a consequence,three is a challenge flow from the society. Having KKN, for community service of civitasacademicians STKIP PGRI Pacitan, forms a response to the dynamic society that isalways closely correlated with the developing issues, needs and faced challenges.